-6(x+7)=-4x-(2)

Simple and best practice solution for -6(x+7)=-4x-(2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+7)=-4x-(2) equation:


Simplifying
-6(x + 7) = -4x + -1(2)

Reorder the terms:
-6(7 + x) = -4x + -1(2)
(7 * -6 + x * -6) = -4x + -1(2)
(-42 + -6x) = -4x + -1(2)

Multiply -1 * 2
-42 + -6x = -4x + -2

Reorder the terms:
-42 + -6x = -2 + -4x

Solving
-42 + -6x = -2 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-42 + -6x + 4x = -2 + -4x + 4x

Combine like terms: -6x + 4x = -2x
-42 + -2x = -2 + -4x + 4x

Combine like terms: -4x + 4x = 0
-42 + -2x = -2 + 0
-42 + -2x = -2

Add '42' to each side of the equation.
-42 + 42 + -2x = -2 + 42

Combine like terms: -42 + 42 = 0
0 + -2x = -2 + 42
-2x = -2 + 42

Combine like terms: -2 + 42 = 40
-2x = 40

Divide each side by '-2'.
x = -20

Simplifying
x = -20

See similar equations:

| 7x-16=-3x | | log(2x)=1 | | -7(x+7)=-6 | | 2(u^-1)^-5/-2u^-9 | | 6=-.5(x)+14 | | 2x+1=11x+46 | | -4x-(7)+10x=-7+6x | | 15x(-23)=-45x(-23) | | 2x^4-4=12 | | 0.5(7d+4)=7-(1.5)d | | ln(x+6)-ln(x-5)=6 | | -5(w-8)+9w+3= | | 0.5n=4.5 | | 9u^2+30=0 | | 2.2+x=6.2 | | (x-9)(x+7)=o | | y=-4x^2+12 | | 0.75+r=1.25 | | sec^2x-tanx-4=0 | | w-8/15=11/15 | | -24-(-18)=x/8 | | x-5.6=4.4 | | 24x+2=6 | | 7x-2(x-3)=5(x+1)+7 | | an=-2n+7 | | 7(2e-1)-(3)=6+6e | | 6y-5=5y-2 | | -7x-3(7x+16)=-188 | | -17=-7-2x | | 259=170-y | | 35-19=2(x-9) | | 2x-16=26-x |

Equations solver categories